Work accidents with children and youth in a rural environment in southern Brazil - Daiani Modernel Xavier; Marta Regina Cezar-Vaz; Clarice Alves Bonow; Maria Denise Schimith
Objective: to know the prevalence of occupational accidents in children and youth who work with their families in the rural environment and to identify the associated factors. Method: exploratory, descriptive and analytical study with quantitative approach, developed in three rural areas. Participants were 211 children and young people who assisted the family in rural work. Data collection was performed using a semi-structured questionnaire. Bivariate analysis was performed using Pearson's chi-square, Fisher's exact, Student's t and Mann-Whitney tests and multivariate analysis using Poisson regression. Results: the prevalence of self-reported occupational accidents was 55%. It was highlighted: insect bites (44%), burns (40.5%), falls (27.6%), injury with a working tool (16.4%), electric shock (15.5 %), burn by animal (8.6%), animal bite (6.9%) and pesticide poisoning (2.6%). These were related to shared housing, leisure activity - riding a motorcycle, product resulting from lettuce cultivation and use of personal protective equipment. Conclusion: it is believed that these findings may enhance the development of public policies aimed at preserving the health of these children and young people, regulate working conditions and reduce occupational risks in the rural environment.